The Analysis of Online Discussion in Improving Students' Learning Motivation in Islamic Religious Education - Milah, Agus Saepul (Devotion : Journal of Research and Community Service, 2022)
This study is motivated by students' low learning motivation in Islamic religious education subjects, which has a significant impact on student learning outcomes, resulting in lower learning achievement in Islamic religious education. Furthermore, the COVID-19 outbreak is presently occurring, requiring at-home education. This exacerbates students' lack of enthusiasm to learn, particularly in Islamic religious education subjects. As a result, an effective approach for increasing students' learning motivation is required, one of which is the employment of the discussion method. The goal of this study was to identify the impact of online discussion in increasing students' learning motivation in Islamic religious education subjects, as well as the elements that hampered and aided its implementation. The methods of observation, interviews, and documentation were utilized in the research, which fits under the category of qualitative research. The research method used was descriptive qualitative research. The study's findings revealed that using online discussions increased students' learning motivation. As for the author's conclusion that using online discussions in Islamic religious education learning can increase students' learning motivation, this can be seen from the results of observations made during discussion activities, where students were very enthusiastic when the discussion took place, and students' learning motivation in every other subject.